Construction of a core-shell microneedle system to achieve targeted co-delivery of checkpoint inhibitors for melanoma immunotherapy. (1st March 2020) - Yang, Peipei; Lu, Chao; Qin, Wanbing; Chen, Minglong; Quan, Guilan; Liu, Hu; Wang, Lili; Bai, Xuequn; Pan, Xin; Wu, Chuanbin
Abstract: Synergistic anti-tumor effect of anti-PD-1/L1 antibody (aPD-1/aPD-L1) and 1-methyl-D, L-tryptophan (1-MT) in melanoma has been well demonstrated, while efficient topical delivery systems are still largely unexplored. Here, a highly drug-concentrated hybrid core-shell microneedle (CSMN) system for co-delivery of checkpoint inhibitors was developed. Based on the specific drug-matrix interaction, the system concentrated aPD-L1 in the tips of microneedles through electrostatic interactions, and increased the amount of 1-MT loaded in CSMN by preventing its premature crystallization using PVA, the material used to prepare CSMN core. The prepared CSMN exhibited high transdermal delivery efficiency and long topical retention time of aPD-L1 for 2 days. Drug-loaded CSMN achieved better anti-tumor efficacy than the intra-tumor injection group at the same dose, which was likely because the former recruited more T lymphocytes to the tumor site. These findings suggested that this CSMN system was a promising local delivery system of both aPD-L1 and 1-MT for melanoma immunotherapy, and its unique core-shell structure could be readily adapted as a modular platform for various diseases, where combination therapy of both biomacromolecular drugs and other small-molecular agents were required. Statement of Significance: In the present study, a core-shell microneedle (CSMN) system was constructed to achieve targeted co-delivery of checkpoint inhibitors to melanoma, while preventing significant systemic exposure. To overcome the drawback of insufficient drug loading of microneedles and effectively encapsulate two drugs simultaneously, microneedles were divided into two independent functional areas, a charged shell and a hydrophilic core and encapsulated drugs based on respective drug-matrix interaction. The charged shell prepared by chitosan could concentrate aPD-L1 in the tips of microneedles through electrostatic interactions. The core prepared by PVA successfully increased the amount of 1-MT loaded in microneedles by preventing its premature crystallization. The prepared CSMN exhibited high transdermal delivery efficiency and better anti-tumor efficacy than intra-tumor injection at the same dose. Graphical abstract: Image, graphical abstract